Cutaneous larva migrans syndrome in travelers returning from warm climate countries - Kacprzak, Elżbieta; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
In Poland about 1 million tourists travel to tropical and subtropical countries each year, so we observe an increasing number of imported exotic diseases, including malaria, amoebiasis and more frequently parasitic skin diseases. Cutaneous larva migrans syndrome (CLM) is caused by a migrating infectious larval form of various animal nematodes of dogs and cats accidentally infecting people, which penetrates the stratum germinativum of the human skin. The larva moves several millimeters to a few centimeters daily and it forms serpiginous linear tunnels. The cutaneous creeping eruption with papulo-vesicular lesions usually develops a few weeks after returning from endemic areas in warmer climates. It causes an intense pruritus, so the skin is scratched and becomes secondarily infected. There is usually no systemic hypereosinophilia. We reported four cases of creeping eruption caused by Ancylostoma brasiliense or Strongyloides stercoralis imported from Thailand and Madagascar, or acquired in the Mediterranean region, successively treated with oral doses of albendazole.